Holding on to childhood things: storage, emotion, and curation of children's material biographies. (12th February 2022) - Owen, Jennifer; Boyer, Kate
ABSTRACT: Young people in the UK, known as 'generation rent', rely on parents to hold on to their childhood things as they find themselves uprooted and 'space poor'. As such lofts, cupboards, and self-storage units are home to dormant objects that do not fit into everyday life but cannot be thrown away. This paper extends existing scholarship by considering the role of material things in how parents and children relate to one another, exploring how parents engage with and manage their children's material biographies as they move into adulthood and away, spatially and emotionally, from their parents and the family home. We ask what caring, curating, and storing children's possessions means in the context of parenting and care-work more generally. Based on two rounds of in-depth interviews with eight middle-class parents in the UK, we argue that caring for material things can serve as a way for both parents and children to manage feelings of nostalgia, or loss, through this transition. We further argue that these practices serve as a form of material-emotional grounding, or effort to generate a sense of security, in the face of uncertainty about what the future may hold in the context of unaffordable housing markets.